Environmental-Based Character Education: Implementation of Lampung Society Life Philosophy Values (Piil Pesenggiri) In Elementary School - Dian Andesta Bujuri; Muqowim; Masnun Baiti; Tutut Handayani; Agra Dwi Saputra; Ayu Nur Shawmi; Fidian Abron (International Journal of Elementary Education, 2023)
The effort to shape students' character is to revitalize the values of local wisdom in Indonesia. The purpose of this study is to analyze the implementation of the importance of the philosophy of life of the Lampung people (Piil Pesenggiri) in forming environmental-based characters in elementary school students. This type of research is qualitative research with a case study approach. The subjects of this study were the principal, 5 teachers, 18 students in grade 2, 20 students in grade 4, and 17 students in grade 5. Data was obtained through observation, documentation, and interviews. The results of the study are as follows. First, the values of the Piil Pesenggiri are not the priority values that are implemented. Second, in theory, the importance of Piil Pesenggiri is only intensely implemented in Lampung language subjects in high grades. In practice, Piil Pesenggiri's values are integrated throughout the curriculum. Third, the character of the students is quite good. However, students need to be made aware that the values practiced are part of the values of the Pesenggiri Piil. The knowledge and appreciation of students regarding the importance of the Pesenggiri Piil still need to improve, even strangers to the term Pesenggiri Piil as a reference for morality or the original character of the people of Lampung. Implementing Piil Pesenggiri values in practice will only fully shape students' character if accompanied by intense knowing and feeling.